Potent immunomodulatory and antitumor effect of anti-CD20-IL2no-alpha tri-functional immunocytokine for cancer therapy - Casadesús, Ana Victoria; Cruz, Beatriz María; Díaz, Wilden; González, Miguel Ángel; Gómez, Tania; Fernández, Briandy; González, Addys; Ledón, Nuris; Sosa, Katya; Castro, Kathleen; López, Armando; Plasencia, Claudia; et al. (Frontiers in Immunology, 2022)
The anti-CD20 antibody rituximab (RTX) has substantially improved outcomes of patients with B-cell lymphomas, although more efficient therapies are needed for refractory or relapsing lymphomas. An approach to increase the clinical effectiveness of anti-tumor therapy is the use of antibody-cytokine fusion proteins (immunocytokines (ICKs)) to deliver at the tumor site the antibody effector functions and cytokines that trigger anti-tumor activities. In particular, IL-2-based ICKs have shown significant results in preclinical studies but not in clinical trials due to the toxicity profile associated to high doses IL-2 and the undesired expansion of Tregs. To improve the efficacy of RTX therapy, we fused a murine (mIgG2a) or a human (hIgG1) version of RTX to a mutated IL-2 (no-alpha mutein), which has a disrupted affinity for the high affinity IL-2 receptor (IL-2R) to prevent the stimulation of Tregs and reduce the binding to endothelial cells expressing CD25, the α chain of high affinity IL-2R. Characterization of anti-CD20-IL2no-alpha ICKs was performed by SDS-PAGE, Western-blotting and SEC-HPLC and also by several functional in vitro techniques like T-cell proliferation assays, apoptosis, CDC and ADCC assays. The in vivo activity was assessed by using murine tumor cells expressing huCD20 in C57/Bl6 mice. Both ICKs exhibited similar in vitro specific activity of their IL2no-alpha mutein moieties and kept CD20-binding capacity. Anti-CD20-IL2no-alpha (hIgG1) retained antibody effector functions as complement-dependent cytotoxicity and enhanced direct apoptosis, NK cell activation and antibody-dependent cellular cytotoxicity relative to RTX. In addition, both ICKs demonstrated a higher antitumor efficacy than parental molecules or their combination in an EL4-huCD20 tumor model in immunocompetent mice. Anti-CD20-IL2no-alpha (hIgG1) strongly expanded NK and CD8+ T cells but not Tregs in tumor-bearing mice. These findings suggest that anti-CD20-IL2no-alpha could represent an alternative treatment for B cell lymphoma patients, mainly those refractory to RTX therapy.